Ectonucleotidase inhibitors: a patent review (2011-2016). (2nd December 2017) - Al-Rashida, Mariya; Qazi, Syeda Uroos; Batool, Nayab; Hameed, Abdul; Iqbal, Jamshed
ABSTRACT: Introduction : Ectonucleotidases are a broad family of metallo-ectoenzymes that are responsible for hydrolysing a variety of nucleotides to nucleosides, hence orchestrating the activation of P1 and P2 cell receptors via controlled release of nucleotides and nucleosides. Many disorders such as impaired calcification including aortic calcification, neurological and immunological disorders, platelet aggregation, cell proliferation and metastasis. are characterized by an increase in expression of these ectonucleotidases. Consequently, selective inhibitors of ectonucleotidases are required for therapeutic intervention. Area covered : Several classes of compounds such as purine, nucleotide derivatives (e.g., ARL67156) and monoclonal antibodies, have shown promising ectonucleotidase inhibitory potential. This review discusses chemistry and therapeutic applications of ectonucleotidase inhibitors patented from 2011 to 2016. Expert opinion : All eukaryotic cells express nucleotide and nucleoside receptors on their cell surface and are capable of releasing extracellular nucleotides. Ectonucleotidases are a broad family of metallo-ectoenzymes that hydrolyze a variety of nucleotides to nucleosides. These extracellular nucleotides and nucleosides are important cell signalling molecules and mediate a variety of (patho)physiological processes by acting upon their respective P1 and/or P2 receptors. Discovery of molecules that can selectively inhibit or activate ectonucleotidases is crucial from therapeutic point of view, since it allows human intervention into purinergic cell signalling, thereby allowing us to modulate related (patho)physiological processes as desired.